C-reactive protein point of care testing and physician communication skills training for lower respiratory tract infections in general practice: economic evaluation of a cluster randomized trial. - Cals, J; Ament, A; Hood, K; Butler, C; Hopstaken, R; Wassink, G; Dinant, G (2011)
RATIONALE, AIMS AND OBJECTIVES: An economic evaluation of general practitioner (GP) use of C-reactive protein (CRP) point of care test, GP communication skills training, and both GP use of CRP and communication skills training on antibiotic use for lower respiratory tract infections (LRTIs) in general practice. METHODS: Cost-effectiveness analysis with a time horizon of 28 days alongside a factorial, cluster randomized trial in 431 patients with LRTIs recruited by 40 GPs. INTERVENTIONS: usual care (control group), GP use of CRP point of care test, GP communication skills training, and both CRP use and communication skills training. MAIN OUTCOME MEASURE: health care costs. Cost-effectiveness, using the primary outcome measure antibiotic prescribing at index consultation, was assessed by incremental cost-effectiveness ratios (ICER). To adjust for skewed data and clustering, we used non-parametric bootstrapping re-sampling to derive percentile intervals for the mean difference in total costs and the mean difference in effectiveness between the groups. Various implementation scenarios according to GP preference were modelled with corresponding net monetary benefit (NMB) curves based on a given willingness-to-pay (λ) for a 1% lower antibiotic prescribing rate. RESULTS: The total mean cost per patient in the usual care group was €35.96 with antibiotic prescribing of 68%, €37.58 per patient managed by GPs using CRP tests (antibiotic prescribing 39%, ICER €5.79), €25.61 per patient managed by GPs trained in enhanced communication skills (antibiotic prescribing 33%, dominant) and €37.78 per patient managed by GPs using both interventions (antibiotic prescribing 23%, ICER €4.15). The interventions are cost-effective in any combination (yielding NMB at no willingness-to-pay), taking into account GPs' preferences where at least 15% of GPs chose to implement the communication skills training. CONCLUSIONS: The two strategies, both singly and combined, are cost-effective interventions to reduce antibiotic prescribing for LRTI, at no, or low willingness-to-pay. Taking GP preferences into account will optimize investment in strategies to reduce antibiotic prescribing for LRTI.